DAMPAK COVID19 TERHADAP MANAJEMEN OPERASIONAL UMKM SEKITAR KAMPUS UNIVERSITAS NEGERI PADANG (UNP) - Rika Septrizarty; Asrul Mulyadin (Ensiklopedia Social Review, 2021)
Pandemi of Covid19 changed human activities. The change can be analyzed in campus life, from offline study to online study. The campus is used to be a central of activities and financial support for people around turned become the low mobility area. Covid-19 get the big impact to the Small Medium Enterprise (SME) located around campus.  This resecarh aims to analyzed the impact of covid-19 to the operational management of SME located araund UNP (Padang State University) and used qualititive method by in depth inetrview. The result of the research, only 30% of SME’s operated during pandemi . the significant impact is the reducing of operational schedule and caused the reducing of human resource/labour/staff. Another findings,  the SME’s relocated to the near of communities area and even change the type of business.Keywords: Operasional Management, Pandemi, Covid19, SME